Neuroablative interventions for cancer-related pain. Issue 9 (September 2022) - Pushparaj, Hemkumar; Gupta, Manish; Sharma, Manohar L.
Abstract: Cancer treatment continues to improve survival rate in cancer patients. This also increases cancer-related pain prevalence. Thus, with advances in cancer treatment, there is an ever-increasing unmet need in cancer pain management. Opioids and adjuvant pain killers help to manage significant numbers. Still significant numbers suffer from intractable treatment resistant pain and thus need other modalities. Neuroablative techniques, although technically more demanding, provide good pain control especially in these patients with limited prognosis. Neuroablative procedures are indicated in cancer patients who have limited life expectancy with severe, opioid-resistant pain. The goal would be to improve the quality of life, reduce analgesic side effects, improve patients' ability to function, socialize, and to reduce the amount of time spent in contact with healthcare providers. When successful, these interventions allow significant reduction in the need for clinic visits. Percutaneous procedures are preferred over open procedures for their lower morbidity. This review provides a brief description of commonly used neurolytic interventions for cancer related pain in our multidisciplinary set-up. Neuroablative procedures, especially percutaneous cervical cordotomy require considerable skill of the physician performing the procedure.